Determination of silicon dioxide in fluorite by ICP OES with closed digestion and boric acid complex reaction - Xiao Wang; Liming Gan; Jiufen Liu; Xin Wei; Xi Wang; Tao He; Na Guo (PLoS ONE, 2025)
Fluorite is widely utilized in the new energy, semiconductor, high-end manufacturing, and steelmaking industries. The silicon dioxide (SiO₂) content is critical for both the quality evaluation of fluorite and the design of beneficiation processes. However, the traditional fusion method suffered from several limitations, including cumbersome pretreatment, silica precipitation during acidification, and significant matrix effects caused by alkali metals introduced during fusion. To address these challenges, this study developed an innovative method employing acid dissolution for the determination of SiO₂ content in fluorite using inductively coupled plasma optical emission spectrometry (ICP OES). This method employs a mixture of nitric acid and hydrofluoric acid in a water bath to digest the sample within a closed system. Systematic optimization experiments were conducted to evaluate key parameters, including the volumes of nitric acid and hydrofluoric acid, digestion time in the water bath, and the quantity of boric acid solution, with the aim of enhancing analytical performance. Complete dissolution of silicon dioxide in fluorite was achieved by treating 0.2000 g of sample with 5.0 mL nitric acid and 2.0 mL hydrofluoric acid, followed by heating at 30 minutes. Subsequently, excess fluoride ions were complexed by adding 10 mL of a 50 mg mL -1 boric acid solution. After dilution, the samples are analyzed by ICP OES. At a dilution factor of 2500, the limit of detection (LOD) for SiO₂ was 0.974 µg g -1 , with a measurement range spanning from 0.0004% to 25%. Method validation was performed by analyzing six fluorite certified reference materials in seven replicates. The results were in good agreement with certified values, with relative errors (RE) ≤ 3.61%. Seven replicate analyses of five real fluorite samples also showed consistency with results obtained using the standard alkaline fusion colorimetric method (GB/T 5159.8–2006), with relative deviations ≤ 2.71% and relative standard deviations (RSD, n = 7) ≤ 3.04%. This method employs nitric acid and hydrofluoric acid under sealed water bath digestion conditions for the dissolution of fluorite samples, effectively preventing the volatilization loss of silicon tetrafluoride formed during the reaction between fluorine and silicon. By introducing boric acid to complex excess fluoride ions, the interference caused by residual hydrofluoric acid is eliminated, thereby enabling the use of conventional sampling systems that are otherwise incompatible with hydrofluoric acid media. This approach facilitates the rapid determination of silicon dioxide in fluorite via acid dissolution combined with ICP OES analysis. The procedure is straightforward, efficient, and cost-effective, significantly enhancing analytical throughput. It is well suited for the routine and high-throughput determination of SiO₂ in large batches of fluorite samples.